The role of CXCR3 and CXCR4 in colorectal cancer metastasis. Issue 2 (3rd July 2012) - Murakami, Teppei; Kawada, Kenji; Iwamoto, Masayoshi; Akagami, Masatoshi; Hida, Koya; Nakanishi, Yuki; Kanda, Keitaro; Kawada, Mayumi; Seno, Hiroshi; Taketo, Makoto Mark; Sakai, Yoshiharu
Abstract Chemokines and their receptors play key roles in leukocyte trafficking and are also implicated in cancer metastasis. We previously demonstrated that forced expression of CXCR3 promotes colon cancer metastasis preferentially to the draining lymph nodes (LNs), with poor prognosis. Using clinical colorectal cancer (CRC) samples, here, we show that expressions of CXCR3 and CXCR4 are significantly higher in metastatic foci within LNs and liver compared to primary tumors, whereas ligands for CXCR3 and CXCR4 are not. We also have demonstrated that some human CRC cell lines constitutively express both CXCR3 and CXCR4, and that activation of CXCR3 strengthens the CXCR4‐mediated cell migration in vitro in a synergistic manner. By constructing SW620 cell lines with reduced expression of CXCR3 and/or CXCR4 using microRNA, we investigated in vivo metastatic activities in a mouse rectal transplantation model. Six weeks after inoculation, CXCR3‐, CXCR4‐, and CXCR3/CXCR4 double‐knockdowns significantly reduced metastasis to LNs, liver and lungs, compared to the control (p < 0.05). Importantly, its suppressive effect on LN metastasis was significantly stronger in CXCR3‐ and CXCR3/CXCR4 double‐knockdowns. In addition, CXCR3‐ and CXCR3/CXCR4 double‐knockdowns significantly decreased the dissemination of cancer cells to liver and lungs, even after 2 weeks. These results indicate that targeting CXCR3 and CXCR4 can be a promising therapy against CRC metastasis.